2020
DOI: 10.1002/bit.27630
|View full text |Cite
|
Sign up to set email alerts
|

Functional expression of eukaryotic cytochrome P450s in yeast

Abstract: Cytochrome P450 enzymes (P450s) are a superfamily of heme‐thiolate proteins widely existing in various organisms. Due to their key roles in secondary metabolism, degradation of xenobiotics, and carcinogenesis, there is a great demand to heterologously express and obtain a sufficient amount of active eukaryotic P450s. However, most eukaryotic P450s are endoplasmic reticulum‐localized membrane proteins, which is the biggest challenge for functional expression to high levels. Furthermore, the functions of P450s r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 95 publications
(123 reference statements)
1
25
0
Order By: Relevance
“…Considering the significance in natural product biosynthesis as well as the low activity of P450s, various strategies have been attempted to address the challenges in functional expression of P450s in yeast. In contrast to previous strategies, such as N-terminal truncation and protein molecular engineering, the establishment of platform strains, especially those with ER expansion, has attracted more attention ( Jiang et al, 2021 ). As most eukaryotic P450s and CPRs are membrane-bound proteins and anchored to the ER outer membranes, ER expansion has been determined to be a generally applicable strategy to improve the functional expression of P450s Emmerstorfer et al found that the overexpression of ICE2 could increase the stability and activity of P450/CPR ( Emmerstorfer et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the significance in natural product biosynthesis as well as the low activity of P450s, various strategies have been attempted to address the challenges in functional expression of P450s in yeast. In contrast to previous strategies, such as N-terminal truncation and protein molecular engineering, the establishment of platform strains, especially those with ER expansion, has attracted more attention ( Jiang et al, 2021 ). As most eukaryotic P450s and CPRs are membrane-bound proteins and anchored to the ER outer membranes, ER expansion has been determined to be a generally applicable strategy to improve the functional expression of P450s Emmerstorfer et al found that the overexpression of ICE2 could increase the stability and activity of P450/CPR ( Emmerstorfer et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although a variety of P450s have been successfully expressed in S. cerevisiae , low expression level and activity have become the biggest challenge for fundamental and biotechnological application studies of P450s ( Jiang et al, 2021 ). Accordingly, different strategies have been implemented to increase the expression level and/or activity of P450s in S. cerevisiae , including N-terminal truncation, protein molecular modification of P450s through protein engineering, and co-expression with CPRs ( Jiang et al, 2021 ). Unfortunately, the effects of these engineering strategies are often varied case by case.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with bacterial cell factories (i.e. Escherichia coli ), the ability of post-translational modifications and the presence of inner membrane systems make yeasts including P. pastoris preferred hosts to express eukaryotic complex proteins, such as cytochrome P450s (CYPs), which are often involved in the biosynthesis of natural products [ 6 ]. When compared with the model yeast Saccharomyces cerevisiae , P. pastoris has the advantage of strong and tightly regulated promoters for high level expression of recombinant proteins [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the growing number of newly characterized CYP, many new heterologous candidates, which possibly have improved substrate preference and high activity in S. cerevisiae could be selected and compared to the ones used in Wernig et al, 2020a. Otherwise, a recent review (Jiang et al, 2020) summarized and discussed frequently applied strategies to improve the expression and performances of heterologous CYP in yeast. These include codon optimization, N-terminal modification, protein engineering, co-expression of CYP and CPR, fusion proteins of CYP-CPR and strain modifications to improve the microenvironment for CYP expression (Jiang et al, 2020). Codon optimization of heterologous genes is a wellestablished strategy that can improve gene expression (Elena et al, 2014).…”
Section: Saccharomyces Cerevisiaementioning
confidence: 99%
“…The activity of eukaryotic CYP requires efficient electron transfer from a CPR redox partner (Munro et al, 2013). A suitable CPR should be co-expressed because endogenous CPRs may not be compatible with the heterologous CYP (Jiang et al, 2020). For the reaction of OA to 8hydroxyoctanoic acid in Wernig et al, 2020a, efficient electron transfer to the CYP was ensured by expression of a cognate CPR.…”
Section: Saccharomyces Cerevisiaementioning
confidence: 99%